Age-related cerebral changes during different n-back tasks: a functional near-infrared spectroscopy study - Zhu, Shizhe; Wang, Qinglei; Kan, Chaojie; Geng, Ayan; Sui, Youxin; Zhuang, Ren; Zhu, Yi; Wang, Tong; Zhu, Lan; Guo, Chuan (Frontiers in Aging Neuroscience, 2024)
Background The n-back task is a widely used paradigm to assess working memory and is commonly applied in research on age-related cognitive decline. However, studies utilizing functional near-infrared spectroscopy (fNIRS) to explore this area are limited. Objective This study aims to investigate age-related differences in brain activation during the n-back task using fNIRS. Methods fNIRS data were collected from 18 elderly and 19 young participants while performing different n-back tasks. Brain activation patterns and peripheral performance were compared between the two groups. Results Significant differences in brain activation patterns were observed between elderly and young participants. Under the 3-back condition, the older group exhibited reduced activation in brain regions adjacent to prefrontal cognitive areas compared to the younger group. Additionally, the older group’s performance plateaued at the 2-back level, along with a decline in prefrontal activation. Conclusion These findings may suggest potential markers for cognitive decline, providing a new target for future screening.